Technological innovations on underground coal gasification and co2 sequestration (2010)
A brief description of the underground coal gasification (UCG) process, combined with the possibility of CO2 sequestration, is presented. Although nowadays there are very few active industrial UCG plants, a number of new projects are under way in different parts of the world aimed to produce regular gas fuel derived from “in situ” coal combustion, despite the environmental advantages resulting from this process. A brief review of those projects is included. The possibility of underground CO2 storage, either with or without simultaneous UCG, is analyzed by taking into consideration the main challenges of its application and the risks associated with integrated solutions, thus requiring innovative solutions.